Thin Capitalization, Financial Distress, and Corporate Governance Impact on Tax Avoidance - Mahmudi; Lasulita, Ahmad Faruq (Sinergi International Journal of Accounting and Taxation, 2025)
Tax avoidance is a problem many countries face that can disrupt the optimization of tax revenues and economic development. Tax avoidance is a strategy commonly used by taxpayers to avoid tax burdens by exploiting legal loopholes. This study investigates the factors affecting tax avoidance in Indonesia. Specifically, this research explores whether tax avoidance is affected by thin capitalization and the financial distress faced by companies. Besides that, this study is also intended to investigate the influence of governance mechanism proxied by independent commissioners, institutional ownership, and audit quality on tax avoidance. Data was obtained from companies listed on the Indonesia Stock Exchange, i.e., manufacturing firms from 2012-2018. There are 573 observation data from 132 manufacturing companies in Indonesia. This study employed multiple linear regression analysis as a preferred research method to test the proposed hypotheses. This research finds that tax avoidance is significantly affected by thin capitalization, financial distress, and audit quality. However, this research did not find any influence of independent commissioners and institutional ownership on tax avoidance